Lexicon used in the Confesiones San Marcos 12.0 website: A study from a lexicographic perspective - Collantes Tafur, William Fernando (2025)
The main objective of this research work is to learn about the words and meanings used by the users of the Confesiones San Marcos 12.0 website. This research is important because it contributes to lexical studies in social networks and demonstrates the creative capacity of language in this virtual space. Regarding the methodology, it should be noted that the selected corpus was collected entirely from the page Confesiones San Marcos 12.0, which classifies this research work within a non-experimental cross-sectional design; descriptive type. The corpus data were obtained within the period from March to May 2022 and were recorded including date, publication number (confession) and user information (names and gender). The lexicographic study consists of 26 entries following the lexicographic guidelines. With these data, the versatility of the language is verified and the diverse forms that linguistic realizations acquire are known.